The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.yrtph.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and in vitro toxicological evaluation of aerosol from a novel tobacco vapor product: A comparison with cigarette smoke

Abstract: The recent rapid increase in the prevalence of emerging tobacco- and nicotine-containing products, such as e-cigarettes, is being driven in part by their reduced-risk potential compared to tobacco smoking. In this study, we examined emission levels for selected cigarette smoke constituents, so-called "Hoffmann analytes", and in vitro toxicity of aerosol from a novel tobacco vapor product (NTV). The NTV thermally vaporizes a nicotine-free carrier liquid to form an aerosol which then passes through tobacco, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…The glo aerosol was not mutagenic in the Ames mutagenicity assay or in the mouse lymphoma [17]. Similarly, no measurable genotoxicity or cytotoxicity features were observed after Ploom TECH use [63], and the biological effects of the Ploom TECH aerosol were also lower than those of conventional cigarette smoke [18].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 88%
See 1 more Smart Citation
“…The glo aerosol was not mutagenic in the Ames mutagenicity assay or in the mouse lymphoma [17]. Similarly, no measurable genotoxicity or cytotoxicity features were observed after Ploom TECH use [63], and the biological effects of the Ploom TECH aerosol were also lower than those of conventional cigarette smoke [18].…”
Section: Potential Impact Of Heated Tobacco On Human Healthmentioning
confidence: 88%
“…3) 8 puffs from a conventional cigarette; neutral red uptake and trypan blue assays were used to measure cytotoxicity -emissions from the HTP damaged bronchial epithelial cells; however, the HTP showed reduced cytotoxicity relative to a combustible cigarette but higher toxicity than an e-cigarette compared with air controls, a significant increase in cytokines levels was observed post-exposure to tobacco smoke but not to the HTP or e-cigarette aerosols a 90-day nose-only inhalation study in rats showed that there were no apparent new toxicity effects in the THS2.2 aerosol, compared with the reference cigarette (3R4F) smoke after 90-day exposure the alanine aminotransferase levels and liver weights were significantly higher in female animals exposed to IQOS than in the case of conventional cigarettes hepatocellular vacuolization was significantly increased in IQOS-exposed female rats, an effect not seen in cigaretteexposed animals the THS2.2 aerosol in contrary to the 3R4F cigarette smoke, did not cause global miRNA downregulation a 90-day nose-only inhalation study in rats showed that systemic toxicity and alterations in the respiratory tract were significantly lower in the rats exposed to the mentholated variant of THS2.2 than in the groups exposed to traditional (3R4F) and mentholated reference cigarettes cigarette smoke induced an inflammatory response, triggered cellular stress responses, and affected sphingolipid metabolism while these effects were reduced or absent during exposure to the THS2.2 aerosol (the mentholated variant) 2 types of tobacco sticks (regular tobacco and menthol flavors); comparison to the results observed after the reference cigarette (3R4F) use -aerosol formed during the heating process had around 90-95% fewer toxicants than the smoke of conventional cigarettes during THP1.0 use, the aerosol was generated in a mechanism of distillation or evaporation; there was very little or no combustion during THP1.0 use in the aerosol of THP1.0, the levels of toxicants were substantially lower than in 3R4F smoke: a reduction of 96.1% on average for 9 substances prioritized for lowering in cigarettes, and 96.8% for 18 substances prioritized by the FDA the levels of nicotine, acetaldehyde, formaldehyde and particulate matter emitted during THP1.0 use exceeded ambient air measurements, but were > 90% reduced relative to cigarette smoke, markers of tobacco combustion were not observed; the residual tobacco smoke odor was significantly lower from THP1.0 than from a conventional cigarette -THP1.0 demonstrated significantly reduced cytotoxicity compared to the reference cigarette exposure -THP1.0 showed reduced activity (little or no activity) in all 10 different toxicity and oxidative-stress endpoints, assessed using normal human bronchial epithelial cells, compared to the reference cigarette to the smoke/aerosol each) -the reference cigarette (3R4F) smoke was substantially greater than that of the THS2.2 aerosol in terms of cytotoxicity levels, alterations in tissue morphology, secretion of pro-inflammatory mediators, impaired ciliary function, and increased perturbed transcriptomes and miRNA expression profiles [63] Japan Tobacco to examine the emission levels for selected cigarette smoke constituents, and in vitro toxicity of the aerosol from a novel tobacco vapor product (the Ploom TECH prototype) and to compare them to the reference cigarette (3R4F) smoke the Ploom TECH prototype, the reference cigarette (3R4F); "Hoffmann analytes" were conducted, the Ames assay and the in vitro…”
Section: Evidence From the Experimental Animal And Cellular Studiesmentioning
confidence: 99%
“…The in vitro test battery included ‘classical’ regulatory genetic toxicology tests that have been used over many years in the assessment of combustible cigarettes ( e.g. [ 19 , 20 ]). This was complemented with contemporary high content screening (HCS) approaches to assess targeted endpoints related to cell health and early indicators of biological effects such as cellular and oxidative stress, as previously described [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…British American Tobacco has developed a product that heats rather than burns tobacco, significantly reducing exposure to smoke toxicants to levels comparable to quitting tobacco [ 10 ]. Japan Tobacco has also introduced a smokeless tobacco product with data reflecting substantially lower exposure to smoke toxicants [ 11 ]. Electronic cigarettes have also demonstrated reduced exposure to smoke toxicants compared to cigarettes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%